Clinical manifestations and dental management of dentinogenesis imperfecta associated with osteogenesis imperfecta: Case report - Halima Abukabbos; Faisal Al-Sineedi (Elsevier, 2013)
Dentinogenesis imperfecta (DI) associated with osteogenesis imperfecta (OI) is a genetic disorder that affects the connective tissues and results in dentine dysplasia. This case report discusses the systemic and dental manifestations of OI and DI in a 4-year-old child, with moderate presentation of both disorders, who was treated at King Fahd Military Medical Complex in Dhahran. Dental treatment included the use of strip and stainless-steel crowns under local anesthesia, as well as behavior modification techniques. Rigorous home care instructions, including reinforcement of the oral hygiene practice and avoidance of any episode that may lead to bone fracture, were discussed with the parents. The case was reevaluated at 3-month follow-up visits, wherein the medical and dental histories were updated, the child's growth was monitored, periodic clinical and radiographic examinations were performed, and the oral hygiene was evaluated via the debris index score and caries risk assessment. Further treatment of the permanent dentition may be needed in the future. Keywords: Dentinogenesis imperfecta (DI), Osteogenesis imperfecta (OI), Clinical manifestations, Medical and dental considerations